2020
DOI: 10.3390/nu12092599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Preschool-Based Family-Involving DAGIS Intervention Program on Children’s Energy Balance-Related Behaviors and Self-Regulation Skills: A Clustered Randomized Controlled Trial

Abstract: The study examines the effects of a preschool-based family-involving multicomponent intervention on children’s energy balance-related behaviors (EBRBs) such as food consumption, screen time and physical activity (PA), and self-regulation (SR) skills, and whether the intervention effects differed among children with low or high parental educational level (PEL) backgrounds. The Increased Health and Wellbeing in Preschools (DAGIS) intervention was conducted as a clustered randomized controlled trial, clustered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…The presumed pathways to children's food consumption in the DAGIS intervention study should therefore be tested further by mediation analyses, as previously discussed [19,20], even though the main effects on children's food consumption in the DAGIS study showed no statistically significant results. Still, the study of intervention effects on children's EBRBs in the DAGIS study showed a tendency towards increasing fruit and vegetable consumption among children in the intervention group [29].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The presumed pathways to children's food consumption in the DAGIS intervention study should therefore be tested further by mediation analyses, as previously discussed [19,20], even though the main effects on children's food consumption in the DAGIS study showed no statistically significant results. Still, the study of intervention effects on children's EBRBs in the DAGIS study showed a tendency towards increasing fruit and vegetable consumption among children in the intervention group [29].…”
Section: Discussionmentioning
confidence: 92%
“…The DAGIS intervention study was conducted in Southern Finland during the school year 2017-2018 [29] as a cluster randomised trial at the preschool level. The aim was to promote 3-6-year old children's healthy EBRBs and self-regulation skills through activities in both preschools and at home.…”
Section: Aim Design and Settingmentioning
confidence: 99%
See 3 more Smart Citations